2019
DOI: 10.1093/mmy/myz031
|View full text |Cite
|
Sign up to set email alerts
|

An aero mycological analysis of Mucormycetes in indoor and outdoor environments of northern India

Abstract: Mucormycosis is an angio-invasive infection, predominantly acquired by inhalation of sporangiospores from the environment. However, the burden of Mucormycetes sporangiospores in the air is not well studied. We aimed to estimate the burden of Mucormycetes spores in the outdoor and indoor (hospital) environment across different seasons in north India. A total of 380 air samples from outdoor (n = 180) and indoor (n = 200) environment were included in the study. Air samples were suctioned using air sampler (100 l/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 27 publications
5
53
0
4
Order By: Relevance
“…The mean spore count of Mucormycetes in outdoor samples ranged between 0.73 to 8.60 cfu/m 3 across different seasons. Within the hospital, the mean spore count was slightly higher in an airconditioned area (0.88–1.72 cfu/m 3 ) compared to a non‐airconditioned area (0.68–1.12 cfu/m 3 ) 21 . R arrhizus was the predominant Mucorales isolated in both indoor and outdoor air 21 …”
Section: Aetiology and Risk Factorsmentioning
confidence: 85%
See 3 more Smart Citations
“…The mean spore count of Mucormycetes in outdoor samples ranged between 0.73 to 8.60 cfu/m 3 across different seasons. Within the hospital, the mean spore count was slightly higher in an airconditioned area (0.88–1.72 cfu/m 3 ) compared to a non‐airconditioned area (0.68–1.12 cfu/m 3 ) 21 . R arrhizus was the predominant Mucorales isolated in both indoor and outdoor air 21 …”
Section: Aetiology and Risk Factorsmentioning
confidence: 85%
“…An ecological study conducted in India revealed the presence of many species of Mucorales in soil 20 . Mucorales are also present in indoor environments such as air conditioning filters 21,22 . A recent study from North India reported large numbers of Mucorales spores in both hospitals and outdoor air 21 .…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…An environmental study on the ecology of Mucorales in Indian soils reported a high prevalence of clinically relevant Mucorales [ 2 ]. Mucorales spores are also highly prevalent in the indoor and outdoor air of the same country [ 10 ]. Patients acquire the infection by inhalation, ingestion or traumatic inoculation of the spores from the environment.…”
Section: Introductionmentioning
confidence: 99%